Gigi Ceria, Karakter Mulia: Pengabdian Transnasional Berbasis Edukasi Terintegrasi pada Siswa Third Culture Kids (TCK) di Sekolah Indonesia Jeddah - Naufal Faryreza Ryanta; Hana Faujiyyah Nur Afifah; Lisa Wahidatul Oktaviani; Tria Puji Lestari; Rina Mutya Suzliana; Dwi Dianita Irawan; Mahrani Mahrani (Calory Journal Medical Laboratory Journal, 2026)
Students of the Indonesian School of Jeddah (SIJ) are predominantly categorized as Third Culture Kids (TCK) who face sociocultural challenges and complex health determinants, including a high risk of dental caries and limited character monitoring outside the classroom. This transnational community service program aimed to evaluate the effectiveness of an integrated educational model using audio-visual media through the “Happy Teeth, Bright Smile” campaign and self-monitoring through the “My Adventure Journal” in improving oral health literacy and students’ character behavior. The study employed a Participatory Action Research (PAR) approach with mixed methods involving 155 elementary and junior high school students. Dental knowledge data were analyzed using the Wilcoxon Signed Ranks test, while journal compliance was calculated descriptively using the Grand Mean method and triangulated with content analysis of parental feedback. The results showed that elementary students’ compliance with daily character missions increased by 28.31%, particularly in the discipline dimension. Among junior high school students, multimedia intervention significantly improved clinical preventive knowledge (p < 0.001), with mean scores increasing from 77.00 to 90.20. Parental feedback indicated improvements in self-regulation, responsibility, and self-confidence. The study concludes that optimizing the Tripartite Partnership among university students, schools, and parents is effective in strengthening psychosocial resilience and students’ basic health independence in a transnational environment.